Muon-pair and tau-pair production in two-photon collisions at LEP - Dova, María Teresa (2004)
The QED processes e+e− → e+e−μ+μ− and e+e− → e+e−τ+τ− are studied with the L3 detector at LEP using an untagged data sample collected at centre-of-mass energies 161 GeV ≤ √s 209 GeV. The τ -pairs are observed through the associated decay of one τ into eνν and the other into ππν. The cross sections are measured as a function of √s. For muon pairs, the cross section of the γ γ → μ+μ− process is also measured as a function of the two-photon centre-of-mass energy for 3 GeV ≤ Wγγ 40 GeV. Good agreement is found between these measurements and the O(α4) QED expectations. In addition, limits on the anomalous magnetic and electric dipole moments of the τ lepton are extracted.